Religious Interpretation and the Pandemics in Indonesia: Whither the Pesantren Kiai Develop Meaning of Tawakkal - Ahmad Yusam Thobroni; Auliya Ridwan (Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
This research examines the impact of Covid-19 on global communities and the subsequent implementation of health protocols such as social distancing, mask-wearing, and handwashing to mitigate health risks, particularly virus-related fatalities. Despite these measures, certain communities display reluctance in adhering to health protocols, leading to a surge in Covid-19 cases. Notably, in Indonesia, Islamic education's role in promoting resistance to Covid-19 health protocols through interpretations of Quranic verses on tawakkal (reliance on God's will) remains understudied. Focusing on selected kiai from Sidoarjo district, East Java, this study delves into the various Quranic interpretations regarding pandemics and their evolution. The research identifies two distinct groups of kiai: one advocating complete reliance on tawakkal, relegating human efforts in combating the virus, and another emphasizing proactive measures before turning to tawakkal. The paper argues that these interpretative differences stem from the kiai's ability to use principles of interpreting al-Qur`ān. Understanding these perspectives highlights the interplay between religious beliefs and public health practices during the pandemic, emphasizing the need for engaging Islamic leaders in promoting effective health protocols for societal well-being.